MRI assessment of pathological stage and surgical margins in anterior prostate cancer (APC) using subjective and quantitative analysis. Issue 5 (11th October 2016) - Schieda, Nicola; Lim, Christopher S.; Idris, Muhammad; Lim, Robert S.; Morash, Christopher; Breau, Rodney H.; Flood, Trevor A.; McInnes, Matthew D.F.
Abstract : Purpose: To evaluate magnetic resonance imaging (MRI) for assessment of extraprostatic extension (EPE) and positive surgical margins (PSM) in anterior prostate cancer (APC). Materials and Methods: With Institutional Review Board approval, 25 APC (>2/3 of tumor anterior to urethra) were assessed using 3T MRI by two blinded radiologists for: size and maximal leading edge of tumor (relative to anterior fibromuscular stroma [AFMS]) on b ≥1000 sec/mm 2 echo‐planar‐MRI fused onto T 2 ‐weighted‐MRI, invasion of AFMS and EPE. Comparisons were performed between APCs by EPE/PSM using chi‐square, multivariable analysis, and receiver operator characteristic (ROC) analysis. Results: The prevalence of EPE and PSM were 52% (13/25) and 36% (9/25). Tumor sizes were larger with EPE (22.5 ± 8.4 vs. 14.7 ± 6.3, P = 0.02) and PSM (23.0 ± 9.3 vs. 16.4 ± 7.0, P = 0.06). Area under ROC curve (AUC‐ROC) for the diagnosis of EPE by tumor size was 0.77 (95% confidence interval [CI] 0.58–0.95); ≥16 mm size = sensitivity/specificity 69.2/66.7%. Maximal leading edge of tumor was greater with EPE (2.4 ± 2.2 vs. –0.2 ± 3.0) and PSM (2.8 ± 2.3 vs. –0.3 ± 2.5), ( P = 0.023, 0.031). AUC‐ROC for diagnosis of EPE/PSM by leading edge was 0.78 (CI 0.57–0.97) and 0.75 (CI 0.56–0.94). A ≥1 mm leading edge yielded sensitivity/specificity of 76.9/75.0% and 77.8/62.5% for diagnosis of EPE/PSM. 60–72% (15–18/25) tumors invaded AFMS (k = 0.74), which was not associated with EPE/PSM ( P = 0.12–0.14). Radiologists' assessment of EPE had sensitivity/specificity of 61.5–69.2/50.0–75.0% (k = 0.53). Conclusion: Tumor size and leading edge of tumor relative to AFMS may enable diagnosis of EPE and positive surgical margins in APC. Level of Evidence : 2 J. MAGN. RESON. IMAGING 2017;45:1296–1303